Gene expression analysis of the innate immune system during early rearing and weaning of meagre (Argyrosomus regius). Issue 94 (November 2019) - Campoverde, Cindy; Milne, Douglas J.; Secombes, Christopher J.; Estévez, Alicia; Gisbert, Enric; Andree, Karl B.
Abstract: The present study is the first report of some representative innate immune genes in meagre ( Argyrosomus regius ) larvae. This study has specifically focused on the growth period from hatching to the juvenile stage, a critical time in marine fish development when reliance on innate immune mechanisms are required for survival. We report molecular cloning of partial open reading frames and expression patterns for some innate immune genes ( c3, cox2, met, lyzc, mxp, myd88, nod2, nod3 ) . In addition, phylogenetic analyses of some of the sequences obtained was performed where confusion among closely allied isoforms may have existed. These results show the met isoform from meagre is met II, an isoform more similar to a homolog described in Larimichthys crocea; lysozyme ( lyzc ) corresponds to the c-type and NOD isoforms ( nod2, nod3 ) separate into different clades confirming their distinctness within a common evolutionary history. Gene expression profiles of innate genes were investigated, for nine developmental stages, from 8 days post-hatching (dph) to 120 dph. Present results demonstrated that c3, cox2, met II, lyzc, mxp, myd88, nod2, and nod3 were expressed in all stages of larval development and displayed distinct expression profiles in separate tissues (kidney, spleen gut and gill). Moreover, expression patterns suggested theses innate immune genes may be influenced by feeding practices, i.e. switching from live prey (rotifer and Artemia ) and weaning onto an inert commercial diet. In addition to evaluating changes in gene expression during early development, this study evaluated the modulation of gene expression by means of in vivo trials in juveniles that were stimulated with PAMPs (LPS, poly I:C, β-glucan). These results revealed significant changes in mRNA levels of target genes in the kidney, spleen, gut and gills. However, expression profiles differed in magnitude depending on the stimulant and/or tissue. These results are discussed in terms of their relevance and potential application in aquaculture practices. Graphical abstract: Image 1 Highlights: The first study to identify the genes for met II, c3, cox2, lyzc, mxp, myd88, nod2 and nod3, in meagre. The timing of expression during on-growing of larval and juvenile meagre, depends on the state of maturity of the organs. Changing from live feed to commercial dry feed induces alterations in expression of some innate immune genes. Using PAMPs, in vitro and in vivo, provides insight to the immune response collectively and in separate tissues Some of the information may be useful for improving larval rearing protocols.